Importance of tree hollows for biodiversity of mites (Acari) in the forest reserve "Śrubita" (Carpathian Mountains, south Poland) - SKubała, Piotr; Gurgul, Beata (Biological Letters, 2011)
Tree hollows harbour a specialized fauna, and mites usually are the most numerous arthropods in this microhabitat. Mite fauna in 3 types of tree hollows was studied in the forest reserve "Śrubita" near Żywiec, at an altitude of about 850 m. In total, 2037 individuals of Acari and 1414 of Oribatida, representing 72 species, were collected. Over 1200 individuals per 100 g dry weight of wood dust were collected from tree hollows. The total number of oribatid species in tree hollows was higher than in the forest floor. Most species (also dominants) were obligate members of communities of a certain type of tree hollows.